2021
DOI: 10.1038/s41598-021-98018-4
|View full text |Cite
|
Sign up to set email alerts
|

Handling of targeted amplicon sequencing data focusing on index hopping and demultiplexing using a nested metabarcoding approach in ecology

Abstract: High-throughput sequencing platforms are increasingly being used for targeted amplicon sequencing because they enable cost-effective sequencing of large sample sets. For meaningful interpretation of targeted amplicon sequencing data and comparison between studies, it is critical that bioinformatic analyses do not introduce artefacts and rely on detailed protocols to ensure that all methods are properly performed and documented. The analysis of large sample sets and the use of predefined indexes create challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Index PCR confirmed that the Illumina primer pair had been indexed to the extended PCR products (called multiplexing), which track the samples at the NGS Illumina step [38][39][40]. Initially, we found that index PCR with extended PCR products (ITS + extension) resulted in situations with undesired bands and primer-dimers (Figure 3h, Table 2), which indicated that the extended PCR product had only been partially amplified (perhaps amplifying only fungal primer pairs).…”
Section: Confirmation Of Indexing For Illumina Library Sequencingmentioning
confidence: 64%
“…Index PCR confirmed that the Illumina primer pair had been indexed to the extended PCR products (called multiplexing), which track the samples at the NGS Illumina step [38][39][40]. Initially, we found that index PCR with extended PCR products (ITS + extension) resulted in situations with undesired bands and primer-dimers (Figure 3h, Table 2), which indicated that the extended PCR product had only been partially amplified (perhaps amplifying only fungal primer pairs).…”
Section: Confirmation Of Indexing For Illumina Library Sequencingmentioning
confidence: 64%
“…For cases when all sampled gametophytes are considered for DNA barcoding (e.g., for revealing the community composition of gametophyte populations), we additionally advocate for this TD‐PCR approach. Notably, TD‐PCR can be applied using indexed primers for a multiplexed amplicon (e.g., Guenay‐Greunke et al, 2021 ) using next‐generation sequencing (NGS) (A. Quinlan and L. Y. Kuo et al, unpublished data). When a sampling size is extensive (e.g., >400 samples), costs can be greatly lowered using NGS amplicon sequencing (to <$1 per sample, by our estimation).…”
Section: Discussionmentioning
confidence: 99%
“…One redundant design that we found particularly useful is where each 5' inline index is associated with a unique 3' Illumina index and each 3' inline index is associated with a unique 5' Illumina index. Such redundancy can be used to effectively detect primer cross-contamination, "index hopping", and template switching events that can occur during library preparation or on the Illumina flow cell (Illumina, 2017;Guenay-Greunke et al, 2021;Kinsler et al, 2022). These processes generate chimeric sequences, which introduce demultiplexing errors that in turn translate into errors in lineage frequency estimates.…”
Section: Inline Indicesmentioning
confidence: 99%
“…They cannot expand the multiplexing capacity, but can help detect some index hopping events (those that occur between the Illumina index and the inline index that are on the same primer). The rate of index hopping is much higher on "patterned flow cell" Illumina machines, so we also recommend using a non-patterned flow cell machine for barcode sequencing whenever possible (Illumina, 2017;Guenay-Greunke et al, 2021;Kinsler et al, 2022).…”
Section: Inline Indicesmentioning
confidence: 99%